Expression and prognostic significance of kallikrein-related peptidase 8 protein levels in advanced ovarian cancer by using automated quantitative analysis - Kountourakis, P.; Psyrri, A.; Scorilas, A.; Markakis, S.; Kowaiski, D.; Camp, R.L.; Diamandis, E.P.; Dimopoulos, M.A. (Thrombosis and Haemostasis, 2009)
Kallikrein-related peptidases, a subgroup of the serine protease enzyme family, are considered to be important prognostic biomarkers in cancer. In this study we sought to determine the prognostic value of kallikrein-related peptidase 8 (KLK8,hK8,KLK-8) in ovarian cancer using a novel method of compartmentalised in situ protein analysis.A tissue array composed of 150 advanced stage ovarian cancers, uniformly treated with surgical debulking followed by platinum-paclitaxel combination chemotherapy,was constructed. For the evaluation of kallikrein-related peptidase 8 protein expression, we used an immunofluorescence-based method of automated in situ quantitative protein analysis (AQUA). Mean follow-up time of the cohort was 34.35 months. One hundred twenty-six of 150 cases had sufficient tissue for AQUA analysis.There were significant correlations between tumour mask KLK8 protein expression levels and clinicopathological variables, including grade (p=0.0011), residual disease (p=0.0063) and clinical response to chemotherapy(p=0.0346). In univariate survival analysis there was a significant correlation between KLK8 tumour mask expression and five years progression-free survival, meanwhile it was not associated with five-year overall survival (p =0.0694). Specifically, low KLK8 expression correlated with better outcome (top vs. bottom quartile, p=0.0319). In multivariate survival analysis, adjusting for well-characterised prognostic variables, tumour KLK8 expression level retained its prognostic significance for progression-free survival (95%Cl: 0.341-1.027, p=0.045). The possibility that KLK8 may be a suitable candidate as a diagnostic and prognostic marker warrants further investigation. © 2009 Schattauer GmbH.
Keywords: Advanced ovarian cancer; AQUA; Kallikrein-related peptidase 8; Prognosis